2010
DOI: 10.1002/mus.21739
|View full text |Cite
|
Sign up to set email alerts
|

Permissive environment for B‐cell maturation in myositis muscle in the absence of B‐cell follicles

Abstract: Myositis muscle contains antigen-matured B-cells and plasma cells. Myositis muscle biopsy specimens were examined for nodular collections of T-cells, B-cells, myeloid dendritic cells, plasma cells, and follicular dendritic cells. Immunoglobulin and B-cell-activating factor (BAFF) transcripts were quantitated. Laser-capture microdissection was used to isolate single plasma cells, and their immunoglobulin transcripts were sequenced. Dense inflammatory infiltrates contained histological elements of ectopic lympho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 26 publications
4
52
1
2
Order By: Relevance
“…Clonally related sequences were isolated from whole muscle sections from ten of the twelve myositis patients, with up to four different clonal sets isolated from each muscle sample. Further studies also support the absence of classical ectopic germinal centre structures and the clonal expansion and maturation of B-cells within inflamed muscle (Salajegheh et al, 2010). Collectively this and our work strongly suggest the participation of antigen-specific B-cell immune responses within the muscle.…”
Section: The Ig V-gene Repertoire and Clonally Proliferating Muscle-supporting
confidence: 81%
See 1 more Smart Citation
“…Clonally related sequences were isolated from whole muscle sections from ten of the twelve myositis patients, with up to four different clonal sets isolated from each muscle sample. Further studies also support the absence of classical ectopic germinal centre structures and the clonal expansion and maturation of B-cells within inflamed muscle (Salajegheh et al, 2010). Collectively this and our work strongly suggest the participation of antigen-specific B-cell immune responses within the muscle.…”
Section: The Ig V-gene Repertoire and Clonally Proliferating Muscle-supporting
confidence: 81%
“…Some patients relapsed as their B-cell pools repopulated and depletion of autoantibody titres was variable (Chung, Genovese, & Fiorentino, 2007;Cooper et al, 2007;Levine, 2005). The potential of B-cells as therapeutic targets is further supported by the elevations in serum levels and gene expression of B-cell activating factor (BAFF) in IM patients, a cytokine crucial for B-cell maturation and survival, which is also thought to play a role in autoantibody production (Krystufkova et al, 2008;Salajegheh et al, 2010). Despite all the evidence described here implicating B-cells and loss of B-cell tolerance in the IM, numerous questions still remain to be resolved, including identification of the stimulating antigens and epitopes, sequence characteristics and pathogenicity of highaffinity, antigen-specific antibodies produced in situ, and the factors regulating and controlling these autoimmune reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Serum levels of Baff are elevated in some patients suffering from IIMs including IBM patients 131. Furthermore, Baff transcripts are markedly increased in muscle tissue from IIM patients compared to nonmyositic controls (IBM>PM>DM) 128. However, serum Baff levels were highest in IIM patients that also had detectable levels of anti‐histidyl‐tRNA‐synthetase antibody Jo‐1, an autoantibody that is extremely rare in IBM 132, 133, 134.…”
Section: Pathomechanisms In Ibmmentioning
confidence: 99%
“…Thus, the TLR overexpression found in IIM muscle points to involvement of innate immunity in the pathogenesis of these diseases and is likely to be a link between innate and adaptive immunity in IIMs. Immunohistochemical and molecular studies have shown that transcriptionally active CD138+ plasma cells -that have undergone affinity maturation and switched their isotype from IgM to IgG or IgA -are abundant in PM muscle (Greenberg, 2007a;Salajegheh et al, 2010b;Cappelletti et al, 2011). In view of the recently demonstrated ability of TLR9 to induce B cells to mature to plasma cell in vitro (Giordani et al, 2009), together with the observed upregulation of TLR9 in this form of myopathy , it is reasonable to hypothesize a role for this receptor in immunoglobulin production in PM.…”
Section: Cytokines Chemokines and Activation Of The Innate Immune Rementioning
confidence: 99%